"Time is our worst enemy:" Lived experiences and intercultural relations in the making of green aluminum. (11th August 2021) - Normann, Susanne
Abstract: Climate change's burden is double for many Indigenous communities: while changing weather‐patterns threaten their ways of life, greenlabeled extractive industries take hold in their territories. This article advances decolonial psychology's engagement with climate change mitigation as a form of green colonization through a multi‐site study of lived experiences among Indigenous and Tribal communities affected by the production of "green aluminum." The study follows aluminum's value and supply chains interconnecting the indigenous Southern Saami people's struggle to defend their reindeer pasturing lands to the booming wind power industry in Norway and the Brazilian Amazon communities' confrontations with bauxite‐mining and alumina refineries. Data material consists of individual interviews ( N = 25), 13 group interviews and participatory observation. Despite sociocultural differences, participants narrated lived experiences of loss of lifeworlds and meaning‐systems resulting from wind power and aluminum production, and harmful experiences with companies and bureaucracy thematized as forms of "bad faith." They discussed different mechanisms of violence and dehumanization in hegemonic green agendas. By highlighting how Green New Deal (GND) proposals in Norway forward aluminum‐smelting as exemplar of just transition and green inclusion, the study's findings suggest that for proliferating GND's to be inclusive and just, their scope must be international and decolonial.